Stylistic features of Yunus Abdullahi's “Yalaimi’s” Arabic praise poems to Prophet Mohammed - Lawal Rahman; Khalil Mohammed Usman Gbodofu (Jurnal Internasional Pendidikan Bahasa Arab, 2021)
Eulogizing the prophet has generated controversies among the Muslims just as this genre of poetry has been mostly ignored and seen as having no significant content. In the Islamic era (Al-AsrulIslami) the prophet permitted Hassan bnThabit to compose poem to defend Islam and praised him. Later he condemned referring to him as Allah or son of Allah as a form praise. The aim of this study is to identify the methods used by the poet to eulogies the Prophet and describe the stylistic feature of the poem. The method of research is descriptive and analytic. The result of the study reveals that the author used three major methods to praise the prophet which include reference to his spiritual status, emphasis on his practices and tradition and describing his religious struggle. The styles used by the author include clarity of language, use of imagery, Iqtibas (adaptation and citation of Quran verses) and rhetorical question. It is recommended therefore, that the poems should be completely translated to English for wider circulation.